2002
DOI: 10.1002/1521-396x(200208)192:2<286::aid-pssa286>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep Ultraviolet AlGaInN-Based Light-Emitting Diodes on Si(111) and Sapphire

Abstract: Ultraviolet light‐emitting diodes (LEDs) with emission wavelength as short as 280 nm, grown by gas source molecular beam epitaxy with ammonia, are described. The typical multi‐quantum well (MQW) structure LED consists of an AlN buffer layer deposited on Si(111) or sapphire, followed by a (Al)GaN buffer layer and two superlattice structures, n‐ and p‐type, with the MQW active region placed between them. Room temperature Hall measurements of n‐ and p‐type AlN/AlGaInN superlattice structures show average hole con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…In contrast, the excitation capabilities of photoluminescence (PL) are limited by the incident photon energy [54][55][56]. As a result, it is easier to study deep UV emission with CL than PL [57][58][59][60]. In addition, whereas one incident photon can generate not more than one e-h pair, one incident electron of energy E produces ∼E/3E g pairs, where E g is the band gap of the material [3,4], i.e.…”
Section: Strong Excitationmentioning
confidence: 99%
“…In contrast, the excitation capabilities of photoluminescence (PL) are limited by the incident photon energy [54][55][56]. As a result, it is easier to study deep UV emission with CL than PL [57][58][59][60]. In addition, whereas one incident photon can generate not more than one e-h pair, one incident electron of energy E produces ∼E/3E g pairs, where E g is the band gap of the material [3,4], i.e.…”
Section: Strong Excitationmentioning
confidence: 99%
“…Thus, various methods have been developed, including p-GaN contact layer [117][118][119][120] and superlattice structures, 38,[121][122][123][124][125][126][127][128][129][130] in order to achieve efficient current injection into Al-rich p-Al x Ga 1-x N.…”
Section: 99mentioning
confidence: 91%
“…To date, most of the work on III-nitride UV photodetectors, inclusive of all types, has relied on bulk-like epilayers. Kipshidze et al [14] reported GaN/ AlGaN MQW in an effort to extend the range of wavelength in LED [18]. As for infrared detectors, other III-V material systems, such as GaAs or InP based, devices containing MQWs in their active region have been successfully designed and demonstrated [15][16][17].…”
Section: Introductionmentioning
confidence: 99%